Biochemistry illustrated : biochemistry and molecular biology in the post-genomic era - Campbell, P. N; Smith, Anthony D; Peters, Timothy J (Elsevier Churchill Livingstone, 2005)
This title gives students of medicine, other health professions and science a coherent account of biochemistry and molecular biology. Over 500 two-colour line illustrations help the reader visualise biochemistry and understand difficult concepts. Gene structure and function are introduced early in the book as they are so central to the control and regulation of biochemical processes. This organisation of content provides the reader with a logical sequence of events that aids learning. * Highly visual presentation of subject * Concentrates on essential core of knowledge * Logical sequence of chapters with nucleic acids and protein synthesis covered at start of book.
Keywords: biochemie; Biochemistry